2012
DOI: 10.2220/biomedres.33.75
|View full text |Cite
|
Sign up to set email alerts
|

BHLH transcription factor DEC2 regulates pro-apoptotic factor Bim in human oral cancer HSC-3 cells

Abstract: DEC1 (BHLHE40/Stra13/Sharp2) and DEC2 (BHLHE41/Sharp1) are basic helix-loop-helix (bHLH) transcription factors that are involved in the regulation of apoptosis, cell proliferation, circadian rhythms and the response to hypoxia. We previously showed the functional effects of DEC1 and DEC2 on apoptosis in human breast cancer MCF-7 cells. However, the roles of DEC1 and DEC2 in oral cancer are poorly understood. We examined whether DEC1 and DEC2 are involved in the regulation of apoptosis in human oral cancer HSC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 28 publications
2
35
0
Order By: Relevance
“…This is also consistent with previous findings (17). Although the mechanism underlying the upregulated expression of BHLHE41 in the process of carcinogenesis has not been elucidated, several studies have indicated that BHLHE41 suppresses apoptosis and enhances genomic instability (25,(44)(45)(46). These findings suggest that the upregulated expression of BHLHE41 is expedient for carcinogenesis in endometrial epithelial cells.…”
Section: Discussionsupporting
confidence: 92%
“…This is also consistent with previous findings (17). Although the mechanism underlying the upregulated expression of BHLHE41 in the process of carcinogenesis has not been elucidated, several studies have indicated that BHLHE41 suppresses apoptosis and enhances genomic instability (25,(44)(45)(46). These findings suggest that the upregulated expression of BHLHE41 is expedient for carcinogenesis in endometrial epithelial cells.…”
Section: Discussionsupporting
confidence: 92%
“…SHARP1 is a basic helix-loop-helix transcription factor that is involved in a number of cellular processes, including proliferation [9], apoptosis [30,31], differentiation [32], and circadian rhythms [33-35]. SHARP1 is generally believed to act as a tumor suppressor, and Montagner, et al [11] recently showed that SHARP1 regulates the invasive and metastatic phenotype of triple-negative breast cancer cells by promoting degradation of hypoxia-inducible factors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we proposed that different effects on the DEC1-related apoptosis may depend on the differences in cellular differentiation (TE 10 cells and MCF-7 cells are well-differentiated carcinoma; and TE 5 cells are poorly differentiated type). Our previous reports showed that DEC2 has antiapoptotic effects in human oral cancer HSC-3 and human breast cancer MCF-7 (23,24). Furthermore, DEC1 and DEC2 had opposite effects on apoptosis in MCF-7; i.e., we speculated that a balance between DEC1 and DEC2 may contribute to the apoptotic pathways.…”
Section: Apoptotic Effects In Cddp-treated Te 10 Cells By Dec1 Knockdmentioning
confidence: 80%
“…We analyzed the effects of CDDP on DEC1/DEC2 apoptosis in human oral squamous cell carcinoma CA9-22 and HSC-3 cells, and showed that DEC2 has anti-apoptotic effects on CDDP-induced apoptosis in HSC-3 cells involving Bim down-regulation (24). We also showed that DEC1 and DEC2 have opposite properties in regulating apoptosis, i.e., DEC2 has anti-apoptotic, whereas DEC1 has proapoptotic effects on human breast cancer MCF-7 cells (15,23).…”
Section: Effects Of Cddp On Dec1/dec2 Expressions In Te 10 and Te 5 Cmentioning
confidence: 99%
See 1 more Smart Citation